Evaluation of injection volumes for the transversus abdominis plane block in dog cadavers: a preliminary trial. (January 2021) - Freitag, Flavio A.V.; Muehlbauer, Eloisa; Gaio, Thalise daS.; dos Santos, Amanda A.M.; Machado, Marcello; Sanchez, Andrea; Duque, Juan C.M.
Abstract: Objective: To evaluate staining of nerve branches after the injection of different volumes during ultrasound-guided transversus abdominis plane (TAP) block in dog cadavers. Study design: Prospective randomized study. Animals: A total of 15 frozen/thawed adult dog cadavers. Methods: Hemiabdomens were randomly allocated to one of four groups. In groups G0.3, G0.6 and G1.0, ropivacaine–methylene blue solution (0.3, 0.6 and 1.0 mL kg –1 in seven, eight and eight hemiabdomens, respectively) was injected at the midpoint between the iliac crest and the last rib at the height of the shoulder. In group G0.3×2 (seven hemiabdomens), two injections (0.3 mL kg –1 ) were performed, caudal to the last rib and cranial to the iliac crest at the same height. Total time for injection was recorded; after 30 minutes, cadavers were dissected and spread of dye was evaluated. Results: Accuracy of injection site was 80% and injection time was 71 (48–120) seconds for all groups together. Craniocaudal spread was 6.4 ± 1.6, 9.1 ± 2.6, 11.4 ± 2.3 and 11.2 ± 3.8 cm for G0.3, G0.6, G1.0 and G0.3×2, respectively [G0.3 to G0.3×2 ( p  = 0.044) and G1.0 ( p  = 0.034)]. There was no difference in dorsoventral spread among groups. Number of ventral nerve branches stained was 3 (2–4), 3 (2–4), 3 (3–4) and 3 (2–4) for G0.3, G0.6, G1.0 and G0.3×2, respectively, including nerve branches from twelfth thoracic to third lumbar (L3) in different proportions among groups. Conclusions and clinical relevance: Results suggest that a single-injection TAP block, using 0.3 mL kg –1, stains comparable number of nerve branches as higher volumes or two-point injection. Despite the volume or technique, consistent staining of the innervation of the caudal abdomen (L1–L3) was observed. Additional cadaveric studies are necessary to identify the optimal technique for complete abdominal wall staining.